Unconditional basic income and parasitism tax as nonconventional tools of state income politics - V. Ostapenko (Вестник университета)
Characteristics of model of the unconditional basic income and parasitism tax are considered, economic and social consequences of payments of the unconditional basic income and collection of a tax on parasitism are defined, their connection with other tools of a state policy of the income is established.